Antigen Load and T Cell Function: A Challenging Interaction in HBV Infection - Ilaria Montali; Andrea Vecchi; Marzia Rossi; Camilla Tiezzi; Amalia Penna; Valentina Reverberi; Diletta Laccabue; Gabriele Missale; Carolina Boni; Paola Fisicaro (Biomedicines, 2022)
Current treatment for chronic HBV infection is mainly based on nucleos(t)ide analogues, that in most cases need to be administered for a patient’s lifetime. There is therefore a pressing need to develop new therapeutic strategies to shorten antiviral treatments. A severe dysfunction of virus-specific T cell responses contributes to virus persistence; hence, immune-modulation to reconstitute an efficient host antiviral response is considered a potential approach for HBV cure. In this perspective, a detailed understanding of the different causes of T cell exhaustion is essential for the design of successful functional T cell correction strategies. Among many different mechanisms which are widely believed to play a role in T cell dysfunction, persistent T cell exposure to high antigen burden, in particular HBsAg, is expected to influence T cell differentiation and function. Definitive evidence of the possibility to improve anti-viral T cell functions by antigen decline is, however, still lacking. This review aims at recapitulating what we have learned so far on the complex T cell–viral antigen interplay in chronic HBV infection.